Towards the implementation of a fully-fledged electronic service for citizens: the case for local government in South Africa - Mayedwa, Mziwoxolo (Department of Information Systems, 2023)
The current literature on e-government implementation in South Africa informs this research that there is no framework to guide the implementation of e-government for local municipalities. The public sector does not adopt models that are designed and developed for their context. SA as a developing nation still battles with the implementation of e-government for local government. The research findings in this research depict that the implementation of electronic services is complicated, stagnant, and incoherent due to various factors that hinder its swift implementation. The research commenced its pursuit to identify the factors that hinder the implementation of e-government through conducting four areas of investigations, firstly, the study investigated 205 existing municipal electronic portals to establish the extent to which eportal offers the relevant e-services to the citizens; secondly, the study conducted a research survey and a sample of 579 citizens gave their perspective about e-government services that they receive from local municipalities; thirdly, the study also evaluated the City of Cape Town electronic services to ascertain its adoption; and finally, the study conducted in-depth interviews with 35 e-government experts to understand the factors that hinder the implementation of e-government in SA. The study selected three social theoretical approaches, namely structuration, activity, and agency theories to address the different contexts of the research. Structuration theory has aided the research to ask critical questions about the social structures in local government that affect implementation. The activity theory was used to provide some guidelines to investigate how e-government activities are implemented within the identified social structure. Finally, the agency theory was used to develop a model to guide the implementation of a successful egovernment model by employing a deductive approach. Keywords: e-government, collaboration, citizens, agents, actors, implementation, structuration theory, activity theory, agency theory, and municipalities